Interdependence of ASEAN Business Cycles - Ong, Hway-Boon; Puah, Chin Hong; Muzafar Shah, Habibullah (FFE-ISAFE, 2006)
This paper examines the interdependence relationship of five ASEAN business cycles, namely, Indonesia, Malaysia, Philippines, Singapore and Thailand. We conducted an augmented VAR of Granger non-causality test and discovered that there is strong interdependence among the ASEAN countries under study. Our empirical findings revealed the existence of bi-directional causality among ASEAN countries, especially Malaysia and Singapore. That is to say, economic shocks or policy implementation by any neighbouring countries may be easily transmitted to another.